Welfare economics and wicked problems in coastal and marine governance. (July 2020) - Groeneveld, Rolf A.
Abstract: Coastal and marine governance has been characterised as a 'wicked' problem due to difficulties in definition, uncertainty, and conflicting perspectives and values. Social Cost-Benefit Analysis (SCBA), which is an application of welfare economics, 'tames' such problems by assuming away many of these complexities. This article reviews the simplifying assumptions underlying SCBA in four major areas. First, welfare-economics and SCBA assume a utilitarian, consequentialist frame and a clear problem delineation, whereas wicked problems are difficult to define and delineate. Second, welfare economics can deal with risk and uncertainty as long as all policy alternatives, states of nature, and success criteria are known, whereas for wicked problems it is not known with certainty which alternatives are to be evaluated and by which criteria, and which states of nature are possible. Third, welfare economics can deal with a variety of perceptions as long as the legitimacy of each perception is uncontested, whereas in wicked problems some stakeholders' or experts' views are contested by others. Fourth, welfare economics can deal with a variety of preferences and hence conflicting interests, as long as all values are individual and substitutable, whereas in wicked problems some values cannot be substituted as they represent 'sacred' values such as religion and identity. Despite its limitations, however, the explicit definition of the assumptions behind SCBA make it a helpful benchmark to determine what makes a given problem in coastal and marine governance wicked. Highlights: Welfare-economics makes simplifying assumptions to 'tame' wicked problems. Assumptions regard definition, uncertainty, and conflicting beliefs and values. Tracing assumptions sets limits to cost-benefit analysis. Tracing assumptions offers benchmark to 'wickedness'.